Analysis of Service Quality and Product Quality on User Loyalty of Point Of Sales (POS) Applications Mediated by User Satisfaction of Point Of Sales (POS) Applications for the Food and Beverage (Fnb) Business Sector in Padang City - M. Fikhriadi Rehan; M. Ma'ruf; Eri Besra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of service quality and product quality of the POS application on the loyalty of POS application users mediated by user satisfaction in the food and beverage (FnB) business sector in Padang City. The data used are primary data obtained from cashiers/baristas/owners of FnB business owners spread across the city of Padang. The sample that will be taken is 85 samples and obtained using the Hair formula, while the sampling technique uses the purposive sampling method because the FnB business sector that can be set as a sample only uses the POS application as their transaction tool. Data analysis used Structural Equation Model (SEM) analysis with the help of Partial Least Suare (PLS) software. The results of this study indicate that Service Quality does not affect User Loyalty mediated by User Satisfaction, while Product Quality has a positive effect on User Loyalty mediated by User Satisfaction.